Combustion of Submillimeter Heptane/Methanol and Heptane/Ethanol Droplets in Reduced Gravity. (12th February 2013) - Aharon, I.; Tam, V. K.; Shaw, B. D.
Abstract : Reduced-gravity experiments were performed on combustion of droplets composed of n-heptane mixed with methanol or ethanol. The initial alcohol mass fraction in a droplet was 0% (pure heptane) or 5%. The experiments were performed at 0.1 MPa and 25°C with air or with ambients of oxygen and helium with oxygen mole fractions of 0.3 or 0.4. Initial droplet diameters were in the range 0.67 mm to 0.92 mm. After considering measurement uncertainties, burning rates decreased appreciably as the initial droplet diameter increased for combustion in air but not for combustion in the oxygen/helium environments. It was also found that addition of either methanol or ethanol did not influence burning rates appreciably and that burning rates were larger for the oxygen/helium environments than for air if initial droplet diameter dependences were accounted for.